A method for preparing diamond based on graphite under normal pressure

Through magnetron sputtering and microwave hydrogen plasma treatment technology, tantalum atom deposition and treatment of graphite samples is realized, and the transformation from graphite to diamond under normal pressure is solved, which solves the preparation problems under high temperature and high pressure conditions in the prior art, and reduces costs and equipment requirements.

CN118062842BActive Publication Date: 2025-04-01ZHEJIANG UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410131992.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2025-04-01
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

The prior art requires extreme conditions of high temperature and high pressure when preparing diamond, resulting in high equipment requirements, low production efficiency, high cost, and difficult to obtain monodispersed tantalum atoms, limiting the phase transition from graphite to diamond.

Method used

The graphite sample was deposition of tantalum atoms using magnetron sputtering physical vapor deposition system, followed by microwave hydrogen plasma treatment, and finally annealing treatment under normal pressure to achieve the transformation from graphite to diamond.

Benefits of technology

The phase transition from graphite to diamond was successfully achieved under normal pressure, reducing equipment requirements and production costs, simplifying the process flow, and obtaining more dispersed tantalum atoms, improving the efficiency of phase transition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004690084410000011
    Figure HDA0004690084410000011
  • Figure HDA0004690084410000012
    Figure HDA0004690084410000012
  • Figure HDA0004690084410000021
    Figure HDA0004690084410000021
Patent Text Reader

Abstract

The present invention discloses a method for preparing diamond based on graphite under normal pressure. The graphite is treated by magnetron sputtering physical vapor deposition and microwave hydrogen plasma, and then annealed under different conditions to convert the graphite into diamond under normal pressure. The process of the present invention is simpler and has lower cost than the high temperature and high pressure method, and has important value for the preparation and application of diamond.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a new method for preparing diamond based on graphite under normal pressure. Background Art

[0002] Diamond has extremely excellent physical and chemical properties, such as high hardness, high thermal conductivity, wide bandgap, strong chemical corrosion resistance, etc. It has extremely broad application prospects in industrial processing, electronic devices, quantum technology and other fields. In particular, as a typical representative of wide bandgap semiconductor materials, diamond is considered to be the most promising material for the preparation of the next generation of high-power, high-frequency, high-temperature and low-power loss electronic devices.

[0003] At present, the main methods for preparing diamonds in industry are high temperature and high pressure and chemical vapor deposition (CVD). The high temperature and high pressure method completely simulates the natural mechanism of natural diamond growth underground. It generally requires pressure and temperature above 10GPa and 3000℃. As an extreme physical condition, high pressure can change the interaction between atoms, adjust its bonding mode, and allow the carbon atoms in graphite to recombine into the structure of diamond. The production conditions of this method are extremely harsh. The pressure required for its phase change is as high as several thousand megapascals or even higher, and the temperature conditions are also as high as several thousand degrees Celsius. The equipment requirements are extremely high, and the production efficiency is low, the preparation cost is high, and the difficulty is great. The CVD method includes microwave chemical vapor deposition and hot wire chemical vapor deposition. Microwave chemical vapor deposition uses microwave energy to excite and decompose gas, and the decomposed gas groups undergo gas-phase chemical reactions on the surface of the substrate to grow diamond. In the microwave plasma chemical vapor deposition method, the plasma is highly accumulated and the impurities in the product are few, but the deposition rate is slow. The hot wire chemical vapor deposition method decomposes the carbon-hydrogen mixed gas by heating the metal wire to deposit diamond on a variety of substrates. However, this method consumes a lot of energy. Therefore, it is of great value to develop new methods for preparing diamond.

[0004] In previous studies, the tantalum atoms that escaped from the tantalum filaments in the hot wire chemical vapor deposition system were deposited on pressed graphite sheets and graphene vertical sheets, which allowed graphite to be transformed into diamond under normal pressure (see authorized patent ZL202210305804.7, accepted patent CN202310059001.2, and accepted patent CN202310639800.7). In the above patents, the hot wire chemical vapor deposition system is used. Since the amount of Ta that overflows is difficult to control, Ta is easy to accumulate, and it is difficult to obtain enough monodisperse tantalum atoms, which limits the occurrence of phase change. Therefore, it is necessary to develop a new method for obtaining monodisperse Ta atoms. In this patent, the inventor deposited tantalum atoms on the graphite sample using a magnetron sputtering physical vapor deposition (PVD) coating instrument, and then used microwave hydrogen plasma to treat it, and obtained monodisperse tantalum atoms in the graphite sample, promoting the graphite / diamond phase change under normal pressure. Summary of the invention

[0005] The present invention provides a new method for preparing diamond from graphite under normal pressure. The method prepares a tantalum-loaded graphite sample through a PVD system, treats the graphite sample with hydrogen plasma using an MPCVD system, and then performs annealing treatment, thereby realizing the transformation of graphite into diamond under normal pressure.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention provides a method for preparing diamond based on graphite under normal pressure, the method comprising the following steps:

[0008] S1: The pretreated graphite sheet A is used as a substrate and placed in a magnetron sputtering device with a tantalum target as a target material. Under a protective atmosphere, the tantalum target is ignited and cleaned before sputtering to obtain a tantalum-loaded graphite sheet;

[0009] S2: The pre-treated graphite sheet B is subjected to the following operations to obtain a graphite sheet with a more dispersed tantalum load:

[0010] Putting the tantalum-loaded graphite sheet in a microwave plasma chemical vapor deposition device together with the tantalum-loaded graphite sheet in step S1 into a hydrogen plasma treatment;

[0011] S3: placing the graphite sheet with more dispersed tantalum loading described in step S2 in a vacuum sealed container, and annealing it in a muffle furnace at 600-1000° C. for 30-180 min (preferably 1000° C. for 120 min) to obtain nano-diamond particles.

[0012] It is a common practice in the art that the graphite sheet is pre-treated by polishing, cleaning, etc. before magnetron sputtering. In the embodiment of the present invention, the pre-treated graphite sheet A described in step S1 and the pre-treated graphite sheet B described in step S2 both refer to graphite sheets that have been pre-treated by polishing, cleaning, etc. The letters are only for the convenience of distinguishing graphite sheets at different stages and have no other special meanings. The graphite sheet (prepared by Beijing Electric Carbon Factory, purity 99.9%) is polished (polished with 2000 mesh and 4000 mesh sandpaper successively), polished (polished with polishing flannel), ultrasonically cleaned in an organic solvent (which can be ethanol or acetone, preferably ethanol) (manufactured by Kunshan Ultrasonic Instrument Co., Ltd., model KQ5200DE, 100W-200W ultrasonic for 15 minutes, preferably 140W), washed with deionized water, and dried (dried with a nitrogen gun) to obtain a pre-treated graphite sheet; the above pre-treatment is to obtain a graphite sheet with a smooth and clean surface.

[0013] Furthermore, the magnetron sputtering equipment in step S1 is a JGP-450 magnetron sputtering equipment.

[0014] Furthermore, the protective atmosphere is an inert gas atmosphere, and in one embodiment of the present invention, it is an argon atmosphere.

[0015] In an embodiment of the present invention, the operation of igniting and target washing is: igniting and target washing for 5 minutes at a bias voltage of -100V and a power supply power of 250W.

[0016] Furthermore, the sputtering conditions are: power supply power of 40-60W, sputtering time of 1-2min (preferably sputtering power of 40W, sputtering time of 1min).

[0017] In the embodiment of the present invention, the operation of step S1 is: the pressure of the reaction chamber is pumped down to 5.0×10 -3 Pa or less, turn on the controller, and turn on the sample stage rotation function. Turn on the argon switch, adjust the argon flow rate to 20sccm through the flowmeter, adjust the air pressure to 0.8Pa (reduce the ignition power, other air pressures are just the subsequent target washing power that needs to be increased, and have no special effect), turn on the bias and sputtering power, adjust the power to the tantalum target to start, and then wash the target (washing the target to remove surface dirt and shielding the substrate during the target washing process is a routine operation of the present invention). After the target washing is completed, adjust the sputtering power supply power to 40-60W, and the sputtering time is 1-2min (preferably the sputtering power is 40W, and the sputtering time is 1min). The surface of the graphite sheet obtained in this step will be loaded with tantalum atoms.

[0018] Furthermore, the conditions of the hydrogen plasma treatment in step S2 are: hydrogen flow rate 100-200 sccm (preferably 100 sccm), working gas pressure 1-2 torr (preferably 1 torr), power 700-2000 W (preferably 1200 W), and treatment time 10-40 min (preferably 20 min).

[0019] In an embodiment of the present invention, the graphite sheet B pretreated in step S3 is placed in a quartz tube, the tube is evacuated and sealed (the sample is placed in a sealed quartz tube close to vacuum), annealed at 600-1000° C. for 30-180 min (preferably 1000° C. for 120 min) in a muffle furnace, and the sample is taken out after annealing.

[0020] In an embodiment of the present invention, the graphite sheet substrate material has a size of 10×10×2 mm and is a polycrystalline graphite sheet with a purity of 99.9%.

[0021] Preferably, the PVD magnetron sputtering equipment is purchased from Shenyang Instrument Co., Ltd., Chinese Academy of Sciences, and the model is JGP-450. The MPCVD equipment is purchased from Tamkang University, Taiwan, and the model is MPR100.

[0022] The present invention particularly recommends the method as follows:

[0023] S1: The pretreated graphite sheet A is used as a substrate and placed in a magnetron sputtering device with a tantalum target as a target material. Under an argon atmosphere, the tantalum target is primed and cleaned and then sputtered to obtain a tantalum-loaded graphite sheet;

[0024] The target washing conditions are: bias voltage -100V, power supply power 250W, and target washing start time 5min; the sputtering conditions are: power supply power 40W, and sputtering time 1min;

[0025] S2: The pre-treated graphite sheet B is subjected to the following operations to obtain a graphite sheet with a more dispersed tantalum load:

[0026] The tantalum-loaded graphite sheet described in step S1 is placed in a microwave plasma chemical vapor deposition device for hydrogen plasma treatment; the conditions of the hydrogen plasma treatment are: hydrogen flow rate 100 sccm, working gas pressure 1 torr, power 1200 W, and treatment time 20 min;

[0027] S3: The tantalum-loaded more dispersed graphite flakes described in step S2 are placed in a vacuum sealed container and annealed in a muffle furnace at 1000° C. for 120 min to obtain nano-diamond particles.

[0028] Under the recommended method, nano-diamond particles of about 8-10 nm can be obtained.

[0029] Compared with the existing process of converting graphite into diamond under high temperature and high pressure, the beneficial effects of the present invention are embodied in the following aspects: (1) the metal tantalum atoms sputtered in the PVD system are deposited on the graphite substrate, and more dispersed tantalum atoms are obtained after microwave hydrogen treatment, so that the graphite is converted into diamond under normal pressure, which has the advantages of low cost, energy saving and environmental protection; (2) the method has low equipment requirements, simple process and easy operation; (3) it provides a more feasible solution for the preparation of diamond based on the phase change of graphite under normal pressure, which has important scientific significance and value for the development of new diamond preparation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope (SEM) image of the intrinsic graphite substrate after pretreatment.

[0031] Figure 2 This is a transmission electron microscope (TEM) image of the intrinsic graphite substrate after pretreatment.

[0032] Figure 3 SEM image of Example 1 (700W-20min-1000℃ annealing-30min).

[0033] Figure 4 TEM image of Example 1 (700W-20min-1000℃ annealing-30min).

[0034] Figure 5 SEM image of Example 2 (1200W-20min-1000℃ annealing-30min).

[0035] Figure 6 TEM image of Example 2 (1200W-20min-1000℃ annealing-30min).

[0036] Figure 7 SEM image of Example 3 (1200W-20min-1000℃ annealing-90min).

[0037] Figure 8 TEM image of Example 3 (1200W-20min-1000℃ annealing-90min).

[0038] Fig. 9 SEM image of Example 4 (1200W-20min-1000℃ annealing-120min).

[0039] Fig.10 TEM image of Example 4 (1200W-20min-1000℃ annealing-120min).

[0040] Fig.11 SEM image of Example 5 (1200W-20min-1000℃ annealing-180min).

[0041] Fig.12 TEM image of Example 5 (1200W-20min-1000℃ annealing-180min).

[0042] Fig.13 SEM image of Example 6 (2000W-20min-1000℃ annealing-30min).

[0043] Fig.14 TEM image of Example 6 (2000W-20min-1000℃ annealing-30min). DETAILED DESCRIPTION

[0044] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0045] Example 1

[0046] (1) A graphite sheet (prepared by Beijing Electric Carbon Factory, purity 99.9%) was ground (using 2000 mesh and 4000 mesh sandpaper successively), polished (using polishing flannel cloth), ultrasonically cleaned in organic solvent ethanol (manufactured by Kunshan Ultrasonic Instrument Co., Ltd., model KQ5200DE, 140W ultrasonic for 15 minutes, cleaned with deionized water, and dried (dried with nitrogen gun) to obtain a pretreated graphite sheet; the above pretreatment is to obtain a graphite sheet with a smooth and clean surface.

[0047] (2) The graphite sheet pretreated in step (1) was used as a substrate and placed on a sample stage in a JGP-450 magnetron sputtering device using a tantalum target as a target material. The pressure in the reaction chamber was pumped down to 5.0×10 -3 Pa, turn on the controller, turn on the sample stage rotation function. Turn on the argon switch, adjust the argon flow rate to 20sccm through the flowmeter, adjust the gas pressure to 0.8Pa, turn on the bias and sputtering power (bias -100V), adjust the power to 250W until the tantalum target is ignited, and then wash the target for 5 minutes. After the time is over, adjust the sputtering power to 40W, and the sputtering time is 1 minute.

[0048] (3) The tantalum-loaded graphite sheet prepared in step (2) and the graphite sheet pretreated in step (1) are placed in a microwave plasma chemical vapor deposition equipment for hydrogen plasma treatment, with a hydrogen flow rate of 100 sccm, an adjusted working gas pressure of 1 torr, a power of 700 W, and a treatment time of 20 min.

[0049] (4) placing the graphite sheet with more dispersed tantalum loading obtained in step (3) into a quartz tube, evacuating the tube and sealing the tube (making the sample in a sealed quartz tube close to vacuum), annealing at 1000° C. for 30 min in a muffle furnace, and cooling in air to complete the annealing process.

[0050] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0051] Figure 1 This is the SEM picture of the intrinsic graphite substrate after pretreatment. The graphite surface is very smooth after treatment.

[0052] Figure 2 This is a TEM image of the intrinsic graphite substrate after pretreatment, which mainly shows the crystal plane information of graphite (002)(100) etc.

[0053] Figure 3 This is the SEM picture of Example 1. The graphite surface is relatively smooth after treatment.

[0054] Figure 4The TEM image of Example 1 shows that nanoparticles with a deep contrast exist in the thin area of ​​the sample from the low-magnification image. SAED-a mainly shows diffraction rings of the (220), (202), (400) and (422) crystal planes of Ta2O5. Figure (b) is an enlarged view of the b area in Figure (a). The FT image FT-b1 of area 1 in Figure (b) shows diffraction information with a crystal plane spacing of 0.206nm, corresponding to the (111) plane of diamond. It can be seen that there are diamond nanoparticles in the sample with a size of about 5nm. Figure (c) is an enlarged view of the c area in Figure (a). The enlarged image c-1 of the black particle 1 shows that there are clear lattice fringes inside the particle. The FT image FT-c1 shows two pairs of diffraction points, and the crystal plane spacing is 0.179nm, corresponding to the (521) plane of Ta, and the angle between the (521) and (521) planes is 70°, which is consistent with the standard angle of the crystal plane angle. The enlarged image c-1 of particle 2 shows clear lattice fringes inside the particle, with a crystal plane spacing of 0.300nm, which is consistent with the crystal plane spacing of Ta2O5 (220) plane. The previous analysis shows that there are nanodiamond particles of about 5nm as well as Ta and Ta2O5 particles in the sample.

[0055] Example 2

[0056] (1) A graphite sheet (prepared by Beijing Electric Carbon Factory, purity 99.9%) was ground (using 2000 mesh and 4000 mesh sandpaper successively), polished (using polishing flannel cloth), ultrasonically cleaned in organic solvent ethanol (manufactured by Kunshan Ultrasonic Instrument Co., Ltd., model KQ5200DE, 140W ultrasonic for 15 minutes, cleaned with deionized water, and dried (dried with nitrogen gun) to obtain a pretreated graphite sheet; the above pretreatment is to obtain a graphite sheet with a smooth and clean surface.

[0057] (2) The graphite sheet pretreated in step (1) was used as a substrate and placed on a sample stage in a JGP-450 magnetron sputtering device using a tantalum target as a target material. The pressure in the reaction chamber was pumped down to 5.0×10 -3 Pa, turn on the controller, turn on the sample stage rotation function. Turn on the argon switch, adjust the argon flow rate to 20sccm through the flowmeter, adjust the gas pressure to 0.8Pa, turn on the bias and sputtering power (bias -100V), adjust the power to 250W until the tantalum target is ignited, and then wash the target for 5 minutes. After the time is over, adjust the sputtering power to 40W, and the sputtering time is 1 minute.

[0058] (3) The tantalum-loaded graphite sheet prepared in step (2) and the graphite sheet pretreated in step (1) are placed in a microwave plasma chemical vapor deposition equipment for hydrogen plasma treatment, with a hydrogen flow rate of 100 sccm, an adjusted working gas pressure of 1 torr, a power of 1200 W, and a treatment time of 20 min.

[0059] (4) placing the graphite sheet with more dispersed tantalum loading obtained in step (3) into a quartz tube, evacuating the tube and sealing the tube (making the sample in a sealed quartz tube close to vacuum), annealing at 1000° C. for 30 min in a muffle furnace, and cooling in air to complete the annealing process.

[0060] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0061] Figure 5 This is the SEM picture of Example 2. After annealing, dense spherical nanoparticles with a size of 100-200 nm are present on the surface of the sample.

[0062] Figure 6 The TEM images of Example 2 show that nano-spherical particles exist in the thin area of ​​the sample from the low-magnification images (Figure a, Figure c). SAED-a mainly shows diffraction rings of the (002), (100), (101) and (110) crystal planes of graphite. Figure (b) shows a high-magnification image of the nanoparticles. In Figure (b), there is a granular-sized area with clear lattice fringes inside the particles. The interplanar spacing is 0.248nm, which is the (111) plane of ic, and is the intermediate phase of the graphite to diamond phase transition. SAED-c mainly shows diffraction rings of the (002), (100), (101) and (110) crystal planes of graphite. Figure (d) shows a high-magnification image of the nanoparticles in Figure (c), showing that there are lattice fringes with a spacing of 0.206nm inside the particles, which is the interplanar spacing of the (111) plane of cubic diamond. The previous analysis shows that there are nano-diamond particles of about 8-10nm in the sample.

[0063] Example 3

[0064] (1) A graphite sheet (prepared by Beijing Electric Carbon Factory, purity 99.9%) was ground (using 2000 mesh and 4000 mesh sandpaper successively), polished (using polishing flannel cloth), ultrasonically cleaned in organic solvent ethanol (manufactured by Kunshan Ultrasonic Instrument Co., Ltd., model KQ5200DE, 140W ultrasonic for 15 minutes, cleaned with deionized water, and dried (dried with nitrogen gun) to obtain a pretreated graphite sheet; the above pretreatment is to obtain a graphite sheet with a smooth and clean surface.

[0065] (2) The graphite sheet pretreated in step (1) was used as a substrate and placed on a sample stage in a JGP-450 magnetron sputtering device using a tantalum target as a target material. The pressure in the reaction chamber was pumped down to 5.0×10 -3 Pa, turn on the controller, turn on the sample stage rotation function. Turn on the argon switch, adjust the argon flow rate to 20sccm through the flowmeter, adjust the gas pressure to 0.8Pa, turn on the bias and sputtering power (bias -100V), adjust the power to 250W until the tantalum target is ignited, and then wash the target for 5 minutes. After the time is over, adjust the sputtering power to 40W, and the sputtering time is 1 minute.

[0066] (3) The tantalum-loaded graphite sheet prepared in step (2) and the graphite sheet pretreated in step (1) are placed in a microwave plasma chemical vapor deposition equipment for hydrogen plasma treatment, with a hydrogen flow rate of 100 sccm, an adjusted working gas pressure of 1 torr, a power of 1200 W, and a treatment time of 20 min.

[0067] (4) placing the graphite sheet with more dispersed tantalum loading obtained in step (3) into a quartz tube, evacuating the tube and sealing the tube (making the sample in a sealed quartz tube close to vacuum), annealing at 1000° C. for 90 min in a muffle furnace, and cooling in air to complete the annealing process.

[0068] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0069] Figure 7 This is the SEM picture of Example 3. After annealing, fewer spherical nanoparticles are produced on the surface of the sample. Compared with annealing for 30 minutes (Example 1), the number of nanoparticles on the surface of the sample is greatly reduced, and the size has no obvious change.

[0070] Figure 8It is the TEM image of Example 3. From the low-magnification image, it can be seen that there are black particles on the thin area of ​​the sample. Figure (b) is an enlarged view of area b in Figure (a). The enlarged view b-1 of Figure (b) shows that there are clear lattice fringes inside the area, and the interplanar spacing is 0.210nm, which is the (111) plane of cubic diamond. Figure (c) is an enlarged view of area c in Figure (a). The FT image FT-c1 of area 1 in Figure (c) shows diffraction information with interplanar spacing of 0.210nm and 0.206nm, corresponding to the (111) plane of diamond, and the angle between (111) and (111) planes is 70°, which is consistent with the standard angle of the interplanar angle. Figure (b) is an enlarged view of area b in Figure (a). The enlarged view b-1 of Figure (b) also shows that there are lattice fringes with a spacing of 0.206nm inside the particles, which is consistent with the interplanar spacing of the (111) plane of cubic diamond. It can be seen that there are diamond nanoparticles in the sample, with a size of about 5-7nm.

[0071] Example 4

[0072] (1) A graphite sheet (prepared by Beijing Electric Carbon Factory, purity 99.9%) was ground (using 2000 mesh and 4000 mesh sandpaper successively), polished (using polishing flannel cloth), ultrasonically cleaned in organic solvent ethanol (manufactured by Kunshan Ultrasonic Instrument Co., Ltd., model KQ5200DE, 140W ultrasonic for 15 minutes, cleaned with deionized water, and dried (dried with nitrogen gun) to obtain a pretreated graphite sheet; the above pretreatment is to obtain a graphite sheet with a smooth and clean surface.

[0073] (2) The graphite sheet pretreated in step (1) was used as a substrate and placed on the sample stage of a JGP-450 magnetron sputtering device using a tantalum target as a target material. The pressure in the reaction chamber was pumped down to 5.0×10 -3 Pa, turn on the controller, turn on the sample stage rotation function. Turn on the argon switch, adjust the argon flow rate to 20sccm through the flowmeter, adjust the gas pressure to 0.8Pa, turn on the bias and sputtering power (bias -100V), adjust the power to 250W until the tantalum target is ignited, and then wash the target for 5 minutes. After the time is over, adjust the sputtering power to 40W, and the sputtering time is 1 minute.

[0074] (3) The tantalum-loaded graphite sheet prepared in step (2) and the graphite sheet pretreated in step (1) are placed in a microwave plasma chemical vapor deposition equipment for hydrogen plasma treatment, with a hydrogen flow rate of 100 sccm, an adjusted working gas pressure of 1 torr, a power of 1200 W, and a treatment time of 20 min.

[0075] (4) placing the graphite sheet with more dispersed tantalum loading obtained in step (3) into a quartz tube, evacuating the tube and sealing the tube (making the sample in a sealed quartz tube close to vacuum), annealing at 1000° C. for 120 min in a muffle furnace, and cooling in air to complete the annealing process.

[0076] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0077] Fig. 9 This is the SEM picture of Example 4. After annealing, spherical nanoparticles exist on the surface of the sample. Compared with the sample annealed for 90 minutes (Example 2), the number of particles on the surface is more and the size is larger.

[0078] Fig.10 The TEM image of Example 4 shows that black nanoparticles exist in the thin area of ​​the sample from the low-magnification image. SAED-a mainly shows diffraction rings of the (002), (100), (101) and (110) crystal planes of graphite. Figure (b) shows a high-magnification image of the nanoparticles. The FT image FT-b1 of area 1 in Figure (b) shows diffraction information with a crystal plane spacing of 0.206nm, which belongs to the (111) crystal plane of diamond. Figure (c) is an enlarged view of area c in Figure (a). The enlarged view c-1 of particle 1 shows clear lattice fringes inside the particle. The FT image FT-c1 shows two pairs of diffraction points, and the crystal plane spacing is 0.206nm, corresponding to the (111) plane of diamond, and the angle between the (111) and (111) planes is 70°, which is consistent with the standard angle of the crystal plane angle. The enlarged image of particle 2 also shows that there are lattice fringes with a spacing of 0.206 nm inside the particle, which is consistent with the interplanar spacing of the cubic diamond (111) plane. The previous analysis shows that diamonds with a size greater than 25 nm were obtained in the sample.

[0079] Example 5

[0080] (1) A graphite sheet (prepared by Beijing Electric Carbon Factory, purity 99.9%) was ground (using 2000 mesh and 4000 mesh sandpaper successively), polished (using polishing flannel cloth), ultrasonically cleaned in organic solvent ethanol (manufactured by Kunshan Ultrasonic Instrument Co., Ltd., model KQ5200DE, 140W ultrasonic for 15 minutes, cleaned with deionized water, and dried (dried with nitrogen gun) to obtain a pretreated graphite sheet; the above pretreatment is to obtain a graphite sheet with a smooth and clean surface.

[0081] (2) The graphite sheet pretreated in step (1) was used as a substrate and placed on the sample stage of a JGP-450 magnetron sputtering device using a tantalum target as a target material. The pressure in the reaction chamber was pumped down to 5.0×10 -3Pa, turn on the controller, turn on the sample stage rotation function. Turn on the argon switch, adjust the argon flow rate to 20sccm through the flowmeter, adjust the gas pressure to 0.8Pa, turn on the bias and sputtering power (bias -100V), adjust the power to 250W until the tantalum target is ignited, and then wash the target for 5 minutes. After the time is over, adjust the sputtering power to 40W, and the sputtering time is 1 minute.

[0082] (3) The tantalum-loaded graphite sheet prepared in step (2) and the graphite sheet pretreated in step (1) are placed in a microwave plasma chemical vapor deposition equipment for hydrogen plasma treatment, with a hydrogen flow rate of 100 sccm, an adjusted working gas pressure of 1 torr, a power of 1200 W, and a treatment time of 20 min.

[0083] (4) placing the graphite sheet with more dispersed tantalum loading obtained in step (3) into a quartz tube, evacuating the tube and sealing the tube (making the sample in a sealed quartz tube close to vacuum), annealing at 1000° C. for 180 min in a muffle furnace, and cooling in air to complete the annealing process.

[0084] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0085] Fig.11 This is the SEM picture of Example 5. After annealing, spherical nanoparticles exist on the surface of the sample. Compared with the sample annealed for 120 minutes (Example 4), the number of particles on the surface is reduced and the size is slightly reduced.

[0086] Fig.12 The TEM images of Example 5 are shown in the low-magnification TEM image (a), which shows that there are nano-spherical particles in the sample. The image (b) is an enlarged image of the b area in the image (a). From the enlarged image of the particle, it can be seen that there are clear lattice fringes inside the particle, and the crystal plane spacing is 0.206nm, which is a cubic diamond (111) plane. It can be seen that there are diamond nanoparticles in the sample, with a size of about 10nm.

[0087] Example 6

[0088] (1) A graphite sheet (prepared by Beijing Electric Carbon Factory, purity 99.9%) was ground (using 2000 mesh and 4000 mesh sandpaper successively), polished (using polishing flannel cloth), ultrasonically cleaned in organic solvent ethanol (manufactured by Kunshan Ultrasonic Instrument Co., Ltd., model KQ5200DE, 140W ultrasonic for 15 minutes, cleaned with deionized water, and dried (dried with nitrogen gun) to obtain a pretreated graphite sheet; the above pretreatment is to obtain a graphite sheet with a smooth and clean surface.

[0089] (2) The graphite sheet pretreated in step (1) was used as a substrate and placed on the sample stage of a JGP-450 magnetron sputtering device using a tantalum target as a target material. The pressure in the reaction chamber was pumped down to 5.0×10 -3 Pa, turn on the controller, turn on the sample stage rotation function. Turn on the argon switch, adjust the argon flow rate to 20sccm through the flowmeter, adjust the gas pressure to 0.8Pa, turn on the bias and sputtering power (bias -100V), adjust the power to 250W until the tantalum target is ignited, and then wash the target for 5 minutes. After the time is over, adjust the sputtering power to 40W, and the sputtering time is 1 minute.

[0090] (3) The tantalum-loaded graphite sheet prepared in step (2) and the graphite sheet pretreated in step (1) are placed in a microwave plasma chemical vapor deposition equipment for hydrogen plasma treatment, with a hydrogen flow rate of 100 sccm, an adjusted working gas pressure of 1 torr, a power of 2000 W, and a treatment time of 20 min.

[0091] (4) placing the graphite sheet with more dispersed tantalum loading obtained in step (3) into a quartz tube, evacuating the tube and sealing the tube (making the sample in a sealed quartz tube close to vacuum), annealing at 1000° C. for 30 min in a muffle furnace, and cooling in air to complete the annealing process.

[0092] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0093] Fig.13 This is the SEM picture of Example 6. After the graphite surface is treated, no obvious nanoparticles appear and the surface is uneven, indicating that the high-power hydrogen plasma treatment has a strong etching effect on the sample.

[0094] Fig.14The TEM image of Example 6 shows that there are many black particles in the thin area of ​​the sample from the low-magnification image. Figure (b) is an enlarged image of area b in Figure (a). The enlarged image b-1 of Figure (b) shows that there are clear lattice fringes inside the area, and the interplanar spacing is 0.207nm, which is the (111) plane of cubic diamond. Figure (c) is an enlarged image of area c in Figure (a). The enlarged image c-1 of area 1 in Figure (c) shows that there are clear lattice fringes inside the particles, and the interplanar spacing is 0.260nm, which is consistent with the interplanar spacing of the (111) plane of TaC. The FT image FT-c2 of area 2 in Figure (c) shows two pairs of diffraction points, with interplanar spacings of 0.213nm and 0.254nm, corresponding to the (111) and (200) planes of IC, and the angle between the (111) and (200) planes is 55°, which is consistent with the standard angle of the crystal plane angle. The previous analysis shows that there are nano-diamond particles of about 3 to 5 nm as well as iC and TaC particles in the sample.

Claims

1. A method for preparing diamond based on graphite under normal pressure, characterized in that The method comprises the following steps: S1: The pretreated graphite sheet A is used as a substrate and placed in a magnetron sputtering device with a tantalum target as a target material. Under a protective atmosphere, the tantalum target is ignited and cleaned before sputtering to obtain a tantalum-loaded graphite sheet; S2: The pretreated graphite sheet B is subjected to the following operations to obtain a graphite sheet with a more dispersed tantalum load: the graphite sheet B and the tantalum-loaded graphite sheet described in step S1 are placed in a microwave plasma chemical vapor deposition device for hydrogen plasma treatment to obtain a graphite sheet with a more dispersed tantalum load; S3: The graphite sheet with a more dispersed tantalum load described in step S2 is placed in a vacuum sealed container and annealed in a muffle furnace at 600-1000° C. for 30-180 min to obtain nano-diamond particles.

2. The method for preparing diamond based on graphite under normal pressure according to claim 1, characterized in that: The pretreated graphite sheet A described in step S1 and the pretreated graphite sheet B described in step S2 are obtained by the following operations: grinding and polishing the graphite sheet, ultrasonically cleaning it in an organic solvent, cleaning it with deionized water, and drying it to obtain the pretreated graphite sheet; the organic solvent is ethanol or acetone.

3. The method for preparing diamond based on graphite under normal pressure according to claim 1, characterized in that: The magnetron sputtering equipment in step S1 is a JGP-450 magnetron sputtering equipment.

4. The method for preparing diamond based on graphite under normal pressure according to claim 1, characterized in that: The protective atmosphere in step S1 is an inert gas atmosphere.

5. The method for preparing diamond based on graphite under normal pressure according to claim 1, characterized in that: The operation of igniting and washing the target in step S1 is: igniting and washing the target for 5 minutes at a bias voltage of -100V and a power supply of 250W.

6. The method for preparing diamond based on graphite under normal pressure according to claim 1, characterized in that: The sputtering conditions in step S1 are: power supply 40-60W, sputtering time 1-2min.

7. The method for preparing diamond based on graphite under normal pressure according to any one of claims 1 to 6, characterized in that: The conditions of the hydrogen plasma treatment in step S2 are: hydrogen flow rate 100-200 sccm, working pressure 1-2 torr, power 700-2000 W, and treatment time 10-40 min.

8. The method for preparing diamond based on graphite under normal pressure according to claim 7, characterized in that: The power in step S2 is 1200W.

9. The method for preparing diamond based on graphite under normal pressure according to any one of claims 1 to 6, characterized in that: The annealing temperature in step S3 is 1000°C.

10. The method for preparing diamond based on graphite under normal pressure according to claim 1, characterized in that The method is: S1: The pretreated graphite sheet A is used as a substrate and placed in a magnetron sputtering device with a tantalum target as a target material. Under an argon atmosphere, the tantalum target is primed and cleaned and then sputtered to obtain a tantalum-loaded graphite sheet; The target washing conditions are: bias voltage -100V, power supply power 250W, and target washing start time 5min; the sputtering conditions are: power supply power 40W, and sputtering time 1min; S2: The pre-treated graphite sheet B is subjected to the following operations to obtain a graphite sheet with a more dispersed tantalum load: Putting the tantalum-loaded graphite sheet in a microwave plasma chemical vapor deposition device together with the tantalum-loaded graphite sheet in step S1 into a hydrogen plasma treatment device to obtain a graphite sheet with a more dispersed tantalum load; the conditions of the hydrogen plasma treatment are: hydrogen flow rate 100 sccm, working gas pressure 1 torr, power 1200 W, and treatment time 20 min; S3: The tantalum-loaded more dispersed graphite flakes described in step S2 are placed in a vacuum sealed container and annealed in a muffle furnace at 1000° C. for 120 min to obtain nano-diamond particles.

Citation Information

Patent Citations

  • A method for preparing diamond based on graphite under low pressure

    CN114751408B

  • A method for preparing nanodiamond based on graphene vertical sheets

    CN116752114B

  • Diamond growth control

    CA779256A

  • Method for preparing diamond based on graphite under normal pressure

    CN116282002A